x/6+3=9
x+18/6=9
x+18=9*6
x+18=54
x=54-18
=36
the answer is 36.
2006-12-11 02:21:11
·
answer #1
·
answered by tarena 2
·
0⤊
0⤋
x/6 + 3 = 9
x/6 = 9-3
x/6 = 6
x = 6*6
x=36
2006-12-11 01:27:07
·
answer #2
·
answered by aadhyagupta 2
·
0⤊
0⤋
when solving for a variable, you need to remember your order of operations. you want to isolate your variable on one side of the equation. so x/6+3-3=9-3 you are left with x/6=6 now divide both sides by 6 and your are left with x=1. Remeber too what you do to one side of the equation, you must do to the other.
2006-12-11 01:29:30
·
answer #3
·
answered by thestral 1
·
0⤊
0⤋
x/6 + 3 = 9
Subtract 3 from both sides:
x/6 = 6
Multiply both sides by 6:
x = 36.
2006-12-11 01:03:44
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
36
2006-12-11 01:04:03
·
answer #5
·
answered by GC 3
·
0⤊
0⤋
36
2006-12-11 01:02:25
·
answer #6
·
answered by spaabroadway 3
·
0⤊
0⤋
You've got your original equation:
x/6 + 3 = 9
Subtract 3 from both sides.
x/6 = 6
Now multiply both sides by 6, so that it won't be under that x anymore.
x = 36
If you've got any questions at all, feel free to email.
2006-12-11 01:04:47
·
answer #7
·
answered by Pendergast 2
·
0⤊
0⤋